PENGUATAN LITERASI DIGITAL SISWA SMK DALAM MENYIAPKAN GENERASI WIRAUSAHA DI ERA VUCA (STUDI PENGABDIAN DI SMK PENGUJI SUKABUMI) - Safitri, Niken; Fathussya'adah, Eva; Suaebah, Ebah (HARUPAT: Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
The rapid development of digital technology and the dynamics of the VUCA era (Volatility, Uncertainty, Complexity, and Ambiguity) require young generations, particularly vocational high school students, to possess adequate digital literacy and entrepreneurial readiness. This community service program aimed to strengthen the digital literacy of vocational high school students in preparing an adaptive and competitive entrepreneurial generation in the VUCA era. The program was conducted through a one-day face-to-face activity on May 22, 2025, at SMK Penguji Sukabumi using a participatory learning approach. The methods employed included interactive lectures, discussions, case studies, and simple simulations on the use of digital platforms for entrepreneurial activities. The results indicated an improvement in students’ understanding of digital literacy concepts, digital ethics and security, as well as the productive use of digital technology. In addition, the program enhanced students’ awareness and interest in entrepreneurship by enabling them to identify digital-based business opportunities relevant to their vocational competencies. This community service activity is expected to serve as a sustainable model for strengthening digital literacy and entrepreneurship in vocational schools.